EMIC waves observed at geosynchronous orbit under quiet geomagnetic conditions (Kp ≤ 1). Issue 2 (27th February 2016) - Park, J.‐S.; Kim, K.‐H.; Shiokawa, K.; Lee, D.‐H.; Lee, E.; Kwon, H.‐J.; Jin, H.; Jee, G.
Abstract: We statistically study the local time distribution of the helium band electromagnetic ion cyclotron (EMIC) waves observed at geosynchronous orbit when geomagnetic activity was low ( K p ≤ 1). In order to identify the geosynchronous EMIC waves, we use high time resolution magnetic field data acquired from GOES 10, 11, and 12 over a 2 year period from 2007 and 2008 and examine the local time distribution of EMIC wave events. Unlike previous studies, which reported high EMIC wave occurrence in the postnoon sector with a peak around 1500–1600 magnetic local time (MLT) during magnetically disturbed times (i.e., storm and/or substorm), we observed that quiet time EMIC waves mostly occur in a region from morning (∼0600 MLT) to afternoon (∼1600 MLT) with a peak around 1100–1200 MLT. To investigate whether the quiet time EMIC wave occurrence has a causal relationship with magnetospheric convection enhancement or solar wind dynamic pressure variations, we performed a superposed epoch analysis of solar wind parameters (solar wind speed, density, dynamic pressure, and interplanetary magnetic field B z ) and geomagnetic indices ( A E and S Y M ‐ H ). From the superposed epoch analysis we found that solar wind dynamic pressure variation is a more important parameter than A E and S Y M ‐ H for quiet time EMIC wave occurrence. Key Points: EMIC waves under quiet geomagnetic conditions EMIC occurrence peak near noon Solar wind dynamic pressure variation is a major factor for quiet time EMIC wave generation